A practical workflow for capillary microsampling in nonclinical studies. (15th February 2019) - Wang, Linna; Wang, Bonnie; Chadwick, Kristina D; Su, Ting; Mangipudy, Raja; Pillutla, Renuka C; Ji, Qin C
Aim: The result of investigation on the procedure of sample handling and bioanalysis of small volume of plasma sample for nonclinical studies stored in 0.5-ml micronic tubes was reported.Results/methodology: Sample integrity of the small volume (25 μl) during long-term storage and the feasibility and data reliability of performing multiple re-assays on the small volume sample using 5 μl aliquot per analysis was evaluated.Conclusion: Integrity was maintained in samples (25 μl) stored for up to 1 month in 0.5-ml micronic tubes at -20°C. A 25 μl sample is sufficient for four-times of re-assays. This evaluation demonstrated the feasibility of this workflow of handling and bioanalysis on small volume plasma sample for GLP studies under the US FDA guidance.